Security in Health Information Management Records through Blockchain Technology: A Review - Yasir Hamid; Rameez Yousuf; Atif Chowhan (Journal of Information Security and Cybercrimes Research, 2023)
Medical records play a crucial role in delivering high-quality healthcare by facilitating accurate diagnosis, treatment, and patient monitoring. However, manual, paper-based record-keeping systems present various challenges, including storage burden and retrieval difficulties. Although electronic medical records (EMRs) have gained popularity, they are not risk-free, such as data manipulation. Inadequate medical records administration contributes to inefficiencies in the healthcare system, increased costs, incorrect diagnoses, and compromised patient care. This literature review investigates the potential of blockchain technology in enhancing medical record management and improving the quality, efficiency, and limitations associated with traditional manual methods. Specifically, the study explores the benefits of utilizing blockchain in medical records management. The findings suggest that blockchain technology can enhance the security, interoperability, and accessibility of medical records thereby mitigating concerns related to data manipulation while providing a more cost-effective and efficient solution for medical records management.